PERAN MAHASISWA ASISTENSI MENGAJAR PROGRAM MERDEKA BELAJAR DI SDIT AL-GHAZALI PALANGKA RAYA - Amanda, Fiza; Rahmah, Yulia (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Teaching assistance is an implementation of the Independent Curriculum which provides an opportunity for students to contribute to education at the elementary to secondary school levels under the guidance of field supervisors. This program is intended for students majoring in teaching or education who want to experience being educators. The objectives of this program include increasing knowledge, developing a sense of responsibility, performance ranking, and contributing to society and the nation. The Palangka Raya Islamic State Institute, as one of the universities implementing this program, collaborates with SDIT Al-Ghazali Palangka Raya, an A-accredited school. Students also play a role in various activities, including teaching in class, reviving the library, and implementing the Bengkel Mengaji program for students who need help reading the Qur'an. In addition, students also participate in activities to commemorate historical days. Through this program, students not only gain practical experience in teaching, but also contribute to improving the quality of education and community life.